Delirium in palliative care: Detection, documentation and management in three settings. Issue 6 (21st October 2013) - Hey, Jennifer; Hosker, Christian; Ward, Jason; Kite, Suzanne; Speechley, Helen
Abstract: Objectives: Delirium is characterized by disturbances of consciousness and changes in cognition that develop rapidly and fluctuate. It is common in palliative care, affecting up to 88% of patients with advanced cancer, yet often remains insufficiently diagnosed and managed. This study sought to compare rates of screening, documentation, and management of delirium across three palliative care settings — two hospices and one hospital team — and to determine whether definitive documentation of delirium as a diagnosis is associated with improved management of the disorder. Methods: A retrospective review of patient case notes was performed in three U.K. palliative care settings for the presence of: cognitive screening tools on first assessment; the term "delirium" as a stated documented diagnosis; documented terms, descriptions, and synonyms suggestive of delirium; and management plans aimed at addressing delirium. Results: We reviewed 319 notes. The prevalence of delirium as a documented diagnosis ranged from 0 to 8.4%, rising to 35.7–39.2% when both documented delirium and descriptions suggestive of delirium were taken into account. An abbreviated mental test score (AMTS) was determined for 19.6 (H1) and 26.8% (H2) of hospice admissions and for 0% of hospital assessments. Symptoms suggestive of delirium were managed in 56.3% of cases in hospital, compared with 66.7 (H1) and 72.2% (H2) in hospices. Significance of results: Use of the term "delirium" was infrequent in both hospital and hospice palliative care settings, as was the use of routine screening. Many identified cases did not receive targeted management. The definitive use of the term as a diagnosis was associated with clearer management plans in hospital patients. The authors suggest that better screening and identification remains the first step in improving delirium management.